Views and opinions of the general public about the reimbursement of expensive medicines in the Netherlands - Féline E. V. Scheijmans; Roosmarijn van der Wal; Margot L. Zomers; Johannes J. M. van Delden; W. Ludo van der Pol; Ghislaine J. M. W. van Thiel (PLoS ONE, 2025)
Objectives Solidarity-based healthcare systems are being challenged by the incremental costs of new and expensive medicines for cancer and rare diseases. To regulate reimbursement of such drugs, the Dutch government introduced a policy instrument known as the Coverage Lock (CL) in 2015. Little is known about the public opinion regarding such policy instruments and their consequences, i.e., reimbursement of some, but not all, expensive medicines. We aimed to identify the preferences of Dutch citizens regarding the reimbursement of expensive medicines, and to investigate the views of the public on the use of the CL as a healthcare policy instrument and their input for improvement. Methods Web-based survey of a representative sample of 1999 Dutch citizens aged 18 years and older (panel of research company Kantar Public). Potential respondents were approached via e-mail. Several policy measures, real-life cases and statements related to the CL were presented in the survey to respondents. Their responses were analysed by tabulating descriptive statistics (proportions and percentages). Results 1179 individuals (response rate 59%) filled in the questionnaire. Although a majority considered the CL policy unjustified, they preferred it to the alternative policy measures that were presented. In four real-life case descriptions of patients in need of expensive medicines, respondents most often indicated effectiveness, lack of availability of alternative treatment and improved quality of life due to treatment as reasons for a positive reimbursement decision. An unfavourable cost-benefit ratio was their main reason to be against reimbursement. Some argued that withholding reimbursement was a way of informing manufacturers that extremely high prices are unacceptable. Conclusion There is public support for patients in need of expensive medicine. Many respondents supported the CL as a reimbursement policy. However, there is a wish to optimize the interpretation of the assessment criteria and the weight these are attributed in decision making about reimbursement of expensive innovative medicine for patients.